Factors affecting phosphorus exports from sites irrigated with abattoir wastewater. (3rd January 2011) - Nash, David; Butler, Craig
Abattoir wastewaters often contain significant quantities of phosphorus, inorganic salts, nitrogen and biodegradable organic materials. The nutrients in abattoir wastewaters are potentially useful for plant production and in many countries the application of abattoir wastewaters to land is considered a preferable option to other forms of treatment. In this paper we investigate the factors that affect the sources, mobilisation and transport of phosphorus from sites irrigated with abattoir or similar wastewaters and conclude that it is the interaction between the wastewater and the soil properties that determines if phosphorus exports from sites irrigated with abattoir wastewater are excessive.